Human sulfotransferase SULT2A1 pharmacogenetics: genotype-to-phenotype studies - Thomae, B A; Eckloff, B W; Freimuth, R R; Wieben, E D; Weinshilboum, R M (The pharmacogenomics journal, 2002)
SULT2A1 catalyzes the sulfate conjugation of dehydroepiandrosterone (DHEA) as well as other steroids. As a step toward pharmacogenetic studies, we have ‘resequenced’ SULT2A1 using 60 DNA samples from African-American and 60 samples from Caucasian-American subjects. All exons, splice junctions and approximately 370 bp located 5′ of the site of transcription initiation were sequenced. We observed 15 single nucleotide polymorphisms (SNPs), including three non-synonymous coding SNPs (cSNPs) that were present only in DNA from African-American subjects. Linkage analysis revealed that two of the nonsynonymous cSNPs were tightly linked. Expression constructs were created for all nonsynonymous cSNPs observed, including a ‘double variant’ construct that included the two linked cSNPs, and those constructs were expressed in COS-1 cells. SULT2A1 activity was significantly decreased for three of the four variant allozymes. Western blot analysis demonstrated that decreased levels of immunoreactive protein appeared to be the major mechanism responsible for decreases in activity, although apparent K m values also varied among the recombinant allozymes. In addition, the most common of the nonsynonymous cSNPs disrupted the portion of SULT2A1 involved with dimerization, and this variant allozyme behaved as a monomer rather than a dimer during gel filtration chromatography. These observations indicate that common genetic polymorphisms for SULT2A1 can result in reductions in levels of both activity and enzyme protein. They also raise the possibility of ethnic-specific pharmacogenetic variation in SULT2A1-catalyzed sulfation of both endogenous and exogenous substrates for this phase II drug-metabolizing enzyme.